Application of Bioflocs Combined with Probiotics for Prevention of Vibrio Parahaemolyticus Infection In White Shrimp (Litopenaeus vannamei) - Fariq Azhar (Airlangga University, 2018)
Shrimp farming with intensive system was causing many problems. The presence of disease problems in shrimp caused by bacteria, viruses, or co-infection was a problem that must be solved. The use of probiotics and biofloc was one way to overcome the existing diseases. In addition, the combination was expected to improve the performance of the shrimp immune system. This study aimed to evaluate the using of biofloc combined with probiotics against vannamei (Litopenaeus vannamei) immune system in the challenge test with V. parahaemolyticus. This research was conducted for 5 months. The treatments were the addition of commercial probiotics in the culture medium with biofloc system on the feed in the form of negative control (without probiotics + without biofloc) (1), positive control (biofloc culture medium and without probiotic adduction) (2), probiotics I + bioflok (3 ), probiotics II + biofloc (4), and probiotics III + bioflok (5). The results obtained for the performance performance of the shrimp immune system that the best in treatment 4 (probiotic II + biofloc) with SR yield of 76.67%, THC of 9.7 x 106 ml-1, and total bacterial count of 1.59 x 107. Keywords: Vannamei, Probiotics, Biofloc, Immune System.